2016
DOI: 10.1590/s1677-5538.ibju.2015.0568
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial anomalies associated with hypospadias. Description of a hospital based population in South America

Abstract: Introduction:Hypospadias is a congenital abnormality of the penis, in which there is incomplete development of the distal urethra. There are numerous reports showing an increase of prevalence of hypospadias. Association of craniofacial malformations in patients diagnosed with hypospadias is rare. The aim of this study is to describe the association between hypospadias and craniofacial congenital anomalies.Materials and Methods:A retrospective review of the Latin-American collaborative study of congenital malfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…Hypospadias is one of the most common congenital anomalies in males [23]. Other series on congenital anomalies also reported hypospadias as the most common anomaly [24,25]. However, Marshal et al and Braga et al reported undescended testis as the most common genitourinary anomaly [7,26].…”
Section: Discussionmentioning
confidence: 99%
“…Hypospadias is one of the most common congenital anomalies in males [23]. Other series on congenital anomalies also reported hypospadias as the most common anomaly [24,25]. However, Marshal et al and Braga et al reported undescended testis as the most common genitourinary anomaly [7,26].…”
Section: Discussionmentioning
confidence: 99%
“…The study by Taye et al, 5 aimed to evaluate risk factors related with congenital anomalies found that the majority (59.9percent) of children was male and incidence of congenital anomalies was none significantly associated with maternal age. Also, Nordenvall et al, 6 reported that parental age was none significantly associated with the incidence of hypospadias.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the prevalence of extra-genital anomalies in hypospadias has been previously reported to range from 12-46% [Schneuer et al, 2015;Fernandez et al, 2016;Lu et al, 2017], the prevalence rate of 22% reported in this study is similar to that in other large cohort studies where information on associated congenital anomalies was systematically collected [Ahmed et al, 2004;Cox et al, 2014;Nixon et al, 2017]. The pattern of extra-genital anomalies that were encountered in this cohort was also similar to that reported before with a disorder of intrauterine growth manifested as being small for gestational age [Ahmed et al, 2004;Nordenvall et al, 2014;Poyrazoglu et al, 2017].…”
Section: Discussionmentioning
confidence: 99%